EP38 Secukinumab provides sustained improvement of enthesitis in patients with ankylosing spondylitis: pooled analysis of four pivotal Phase 3 studies. (20th April 2020) - Barkham, Nick; Schett, Georg; Baraliakos, Xenofon; van den Bosch, Filip; Deodhar, Atul; Gensler, Lianne S; Ǿstergaard, Mikkel; Agawane, Shital; Gupta, Ayan Das; Mpofu, Shephard; Fox, Todd; Winseck, Adam; et al.
Abstract: Background: Enthesitis can be a debilitating extra-articular spondyloarthritis manifestation that causes considerable pain and reduced quality of life. We evaluated the effect of secukinumab on axial and peripheral enthesitis in ankylosing spondylitis (AS) patients with baseline enthesitis (BLE) across all MASES sites (N = 13), axial MASES sites (N = 11; 13 MASES minus Achilles tendons [AT] [AxS]), peripheral sites (N = 6; AT + lateral condyles of humerus/femur [PS]) and the AT (N = 2) at Weeks 16 and 52. Methods: This post-hoc analysis pooled data across four AS studies (MEASURE 1-4) from patients originally randomised to secukinumab 150 mg (approved AS dose), 300 mg (MEASURE 3 only) or placebo with BLE (MASES >0). Evaluations included mean change from baseline in MASES score, complete resolution (CR; MASES=0) and improvement from baseline in MASES score ≥5 counts. Mixed-effect model repeat measurement analysis was performed on change from baseline in MASES score and non-responder imputation for resolution of enthesitis at Week 16; data are reported as observed at Week 52. Results: 355 (70.4%), 58 (76.3%) and 280 (72%) patients had BLE in the 150 mg, 300 mg and placebo groups, respectively. Baseline characteristics were comparable across groups. At Week 16, mean change from baseline for overall MASES and at AxS was greater for secukinumab 150 mg (−2.4, −2.3) and 300 mg (−2.9, −2.9) vs placebo (−1.9, −1.8; P < 0.05, P < 0.01). At Week 16, patients treated with secukinumab 150 mg (40.8%, 42.7%) and 300 mg (36.2%, 42.1%) vs placebo (28.9%, 30.1%) achieved CR of enthesitis at overall MASES and AxS. Secukinumab 150 mg and 300 mg were consistently associated with a higher mean change in MASES and CR of enthesitis at PS and AT vs placebo. More patients treated with secukinumab 150/300 mg vs placebo achieved a higher threshold of improvement (≥5 counts) in overall MASES at Week 16. Further improvements were observed for all endpoints at Week 52 (Table 1 ). Conclusion: Secukinumab 150 mg and 300 mg were associated with a higher mean change in MASES and CR of enthesitis for overall MASES and at AxS vs placebo in AS patients at Week 16, which further improved through Week 52. Disclosures: N. Barkham Grants/research support; Novartis, Eli Lilly, UCB, Celgene. G. Schett None. X. Baraliakos Consultancies; AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Chugai, Janssen Biologics, Novartis, Pfizer, UCB Pharma, Galapagos. Member of speakers' bureau; AbbVie, Chugai, Janssen, Novartis, Pfizer, UCB Pharma. Grants/research support; AbbVie, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Chugai, Janssen, MSD, Novartis, Pfizer, Roche, UCB. F. van den Bosch Consultancies; AbbVie, Bristol-Myers Squibb, Galapagos, Janssen, Lilly, Merck, Novartis, Pfizer, UCB. Member of speakers' bureau; AbbVie, Bristol-Myers Squibb, Janssen, Lilly, Merck, Novartis, Pfizer, UCB. A. Deodhar Consultancies; AbbVie, Amgen, Bristol-Myers Squibb, Boehringer Ingelheim, Eli Lilly, Janssen, Novartis, Pfizer, UCB. Grants/research support; AbbVie, Amgen, Eli Lilly, GSK, Janssen, Novartis, Pfizer, Bristol-Myers Squibb, Boehringer Ingelheim, UCB. L.S. Gensler Consultancies; Novartis, Lilly, Janssen. Grants/research support; AbbVie, Amgen, UCB Pharma. M. Ǿstergaard Consultancies; AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, UCB. Member of speakers' bureau; AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, UCB. Grants/research support; AbbVie, Celgene, Centocor, Merck, Novartis. S. Agawane Other; Employee of: Novartis. A. Das Gupta Other; Employee of: Novartis. S. Mpofu Other; Employee of: Novartis. T. Fox Other; Employee of: Novartis. A. Winseck Other; Employee of: Novartis. A. Shete Shareholder/stock ownership; Novartis. Other; Employee of: Novartis. B. Porter Shareholder/stock ownership; Novartis. Other; Employee of: Novartis.